Multi-objective context-guided consensus of a massive array oftechniques for the inference of Gene Regulatory Networks - Segura Ortiz, Adrián; García-Nieto, José Manuel; Aldana-Montes, José Francisco; Navas-Delgado, Ismael (Elsevier, 2024)
Background and Objective: Gene Regulatory Network (GRN) inference is a fundamental task in biology and medicine, as it enables a deeper understanding of the intricate mechanisms of gene expression present in organisms. This bioinformatics problem has been addressed in the literature through multiple computational approaches. Techniques developed for inferring from expression data have employed Bayesian networks, ordinary differential equations (ODEs), machine learning, information theory measures and neural networks, among others. The diversity of implementations and their respective customization have led to the emergence of many tools and multiple specialized domains derived from them, understood as subsets of networks with specific characteristics that are challenging to detect a priori. This specialization has introduced significant uncertainty when choosing the most appropriate technique for a particular dataset. This proposal, named MO-GENECI, builds upon the basic idea of the previous proposal GENECI and optimizes consensus among different inference techniques, through a carefully refined multi-objective evolutionary algorithm guided by various objective functions, linked to the biological context at hand. Methods: MO-GENECI has been tested on an extensive and diverse academic benchmark of 106 gene regulatory networks from multiple sources and sizes. The evaluation of MO-GENECI compared its performance to individual techniques using key metrics (AUROC and AUPR) for gene regulatory network inference. Friedman’s statistical ranking provided an ordered classification, followed by non-parametric Holm tests to determine statistical significance.
Keywords: Genes; Gene regulatory network; Inference; Expression data; Multi-objective evolutionary algorithm; Consensus